Значення ендотеліальної дисфункції та порушень ліпідного обміну у патогенезі кардіоміопатії за цукрового діабету 2-го типу - Сергієнко, В. О. (Clinical Endocrinology and Endocrine Surgery, 2010)
The aim of this study was to investigate the features of circulation insulin, C-peptide, leptin, lipids, hs-CRP, TNF-б, IL-8, soluble adhesion molecule CD31/PECAM-1 concentrations, parameters of insulin resistance and correlation between them in type 2 diabetes mellitus patients (DM) with cardiomyopathy. It was established a considerable increase of circulation insulin, C-peptide, concentrations in blood plasma, HOMA — insulin resistance and decrease of QUICKI-indexes in patients with type 2 DM and functional stage of diabetic cardiomyopathy. Correlation between triglycerides concentrations and parameters of insulin resistance was found. Concentration of endothelin-1 was increased in patients with type 2 DM and subclinical diabetic cardiomyopathy that could be estimate as early marker of diabetic cardiomyopathy. In patients with Type 2 DM and functional stage of diabetic cardiomyopathy type IV of dyslipoproteinemia, in patients with Type 2 DM and functional-organic stage of diabetic cardiomyopathy IIB type of dyslipoproteinemia, that could be evidence of high risk of atherosclerosis, especially of coronary vessels, was found. It was established a considerable increase of hs-CRP, TNF-б, soluble adhesion molecule CD31/PECAM-1 in patients with type 2 DM and functional stage of diabetic cardiomyopathy, IL-8, endothelin-1 and myoglobin in patients with type 2 DM and functional-organic stage of diabetic cardiomyopathy. Correlation between hyperinsulinemia, parameters of insulin resistance, C-peptide, hyperleptinemia, dyslipoproteinema, inflammation factors, endothelin-1 and myoglobin (metabolic syndrome factors) was found.